Earnings and Community College Field of Study Choice in Canada - Brahim Boudarbat (Institute for the Study of Labor (IZA), 2004)
In this paper, we estimate a structural model of choice of field of study by community college students. We use data from the Canadian Survey of Graduates for 12,871 individuals who successfully completed their programs in Canadian community colleges (CEGEPs in Quebec) in 1990 and 1995. Over this period, the returns to fields such as health declined relative to other fields such as science and engineering, a fact that provides useful leverage for identifying the impact of earnings on the choice of field of study. Results indicate that the probability of selecting a specific college field of study depends significantly on expected earnings in this field relative to other fields. We also find that women put less weight on earnings than men when choosing a field of study and those students who were employed prior to starting college are more sensitive to earnings variations across fields of study than students with no prior work experience.
Keywords: J24; J31; 330; Canada; community college; field of study choice; selection bias; Studium; Berufswahl; Einkommen; Lohn; Erwartungstheorie; Schätzung; Kanada